STAT3 inhibition attenuates the progressive phenotypes of Alport syndrome mouse model. Issue 2 (17th August 2017) - Yokota, Tsubasa; Omachi, Kohei; Suico, Mary Ann; Kamura, Misato; Kojima, Haruka; Fukuda, Ryosuke; Motomura, Keishi; Teramoto, Keisuke; Kaseda, Shota; Kuwazuru, Jun; Takeo, Toru; Nakagata, Naomi; et al.
Abstract: Background: Alport syndrome (AS) is a hereditary, progressive nephritis caused by mutation of type IV collagen. Previous studies have shown that activation of signal transducer and activator of transcription 3 (STAT3) exacerbates other renal diseases, but whether STAT3 activation exacerbates AS pathology is still unknown. Here we aim to investigate the involvement of STAT3 in the progression of AS. Method: Phosphorylated STAT3 expression was assessed by immunoblotting analysis of kidneys and glomeruli of an AS mouse model ( Col4a5 G5X mutant). To determine the effect of blocking STAT3 signaling, we treated AS mice with the STAT3 inhibitor stattic (10 mg/kg i.p., three times per week for 10 weeks; n = 10). We assessed the renal function [proteinuria, blood urea nitrogen (BUN), serum creatinine] and analyzed the glomerular injury score, fibrosis and inflammatory cell invasion by histological staining. Moreover, we analyzed the gene expression of nephritis-associated molecules. Results: Phosphorylated STAT3 was upregulated in AS kidneys and glomeruli. Treatment with stattic ameliorated the progressive renal dysfunction, such as increased levels of proteinuria, BUN and serum creatinine. Stattic also significantly suppressed the gene expression levels of renal injury markers ( Lcn2, Kim-1 ), pro-inflammatory cytokines ( Il-6, KC ), pro-fibrotic genes ( Tgf-β, Col1a1, α-Sma ) and Mmp9 . Stattic treatment decreased the renal fibrosis congruently with the decrease of transforming growth factor beta (TGF-β) protein and increase of antifibrosis-associated markers p-Smad1, 5 and 8, which are negative regulators of TGF-β signaling. Conclusion: STAT3 inhibition significantly ameliorated the renal dysfunction in AS mice. Our finding identifies STAT3 as an important regulator in AS progression and provides a promising therapeutic target for AS.